Signaling with Dividends and Share Repurchases: A Choice between Deterministic and Stochastic Cash Disbursements - Hausch, Donald B.; Seward, James K. (Review of Financial Studies, 1993)
We study firms signaling with cash disbursements and show that the choice of a deterministic or a stochastic disbursement depends on a property of the firm’s production function that is analogous to absolute risk aversion for a utility function. With decreasing (increasing) absolute risk aversion, the high-quality firm prefers to distinguish itself from the low-quality firm with a stochastic (deterministic) outlay. We then study in detail two common forms of corporate cash distributions: dividends, a deterministic disbursement, and share repurchases, a stochastic disbursement.